Radius morphometry – A dry bone study (Panacea Journal of Medical Sciences, 2024)
Introduction: Normal values of morphometric parameters of frequently fractured bones of the population we live with is important. Radius is one such bone. In this study, less frequently studied features of radius are measured and compared to find a correlation between them. This is of surgical importance in reconstruction of radius and also in designing implants.Materials and Methods & Results: 105 radius bones from the Anatomy department and students were studied, radial head diameter in two dimensions was measured and averaged. The radial bow length measured from radial tuberosity to proximal end of distal RadioUlnar joint facet. Maximum Bow is measured by the modified method of Schemitsch and Richards. Distal radial metaphysical thickness on either side of the Lister’s tubercle and breadth of the distal end at the level of the distal radioulnar joint was measured using a digital Vernier caliper. Statistical analysis was performed using Minitab® 17.1.0., © 2013 Minitab Inc. All data distribution analysis was checked using the Shapiro-Wilk test.  Correlation statistics were used to establish the relationship between two variables such as radial bow length with proximal and distal end parameters. The average diameter of the radial head was 20.11 mm SD 1.860. The mean Radial bow length was 19.52cm SD1.301. Mean maximum bow 9.105 SD 1.956 mm. The thickness of the distal end medially 17.80mm SD 1.593, lateral to Lister’s tubercle was 15.39 SD1.417.Conclusion: The correlation between different parameters is significant. Bow length and maximum bow are in constant relation. Different part of the radius is in proportion and is an important clinical feature to be appreciated.